Рятівні розкопки в Полтавському та Шишацькому р-нах Полтавської обл. - Гейко, А.В.; Сапєгін, С.В.; Щербань, А.Л. (Археологічні дослідження в Україні, 2010)
Materials of excavations in Poltava Oblast of a barrow of the 7th – the first half of the 6th c. BC of Malyi Trostyanets burial ground and of Shyshaky necropolis of the Scythian period and Chernyakhivska culture are published in the paper.